Comparative feedlot performance of Washera and Horro sheep fed different roughage to concentrate ratio - Gizachew, A. (Haramaya University, 2012)
A study was conducted using thirty male intact Washera and Horro sheep (15 from each breed) with initial body weight (BW) of 19.01±0.37 kg (mean ± SD) to compare feed intake, digestibility, growth performance and carcass characteristics of the animals fed diet containing hay:concentrate ratio of 70:30 (L), 60:40 (M), 50:50 (H). The concentrate contained 30:70 (noug seed cake:wheat bran). Animals of each breed were blocked based on initial BW and were randomly assigned to the dietary treatments. The experimental design was therefore a 2*3 factorial in RCBD. The experiment had a 90 days feeding and 7 days digestibility trials and carcass evaluation at the end. The crude protein (CP) contents of the three diets were 13.7, 15.5 and 18.1% for L, M and H, respectively. Daily dry matter (DM) and CP intakes were only affected by diet (P < 0.05). Intake of DM (720, 812 and 859 g/day (SEM = 22.9)) was lower for L, but was similar (P > 0.05) for M and H. CP intake (105, 130 and 160 g/day (SEM = 3.5) was in the order of L < M < H (P < 0.05). The apparent digestibility coefficients of DM and CP were unaffected (P > 0.05) by genotype, diet or their interaction and were above 60%. Average daily body weight gain (ADG) were significantly impacted only by diet (P < 0.05), and ADG (37, 46, 54 (SEM = 4.0)) was greater (P < 0.05) for H than L with value for M being similar to L and H. Effect of genotype and diet x genotype interaction failed to be significant (P > 0.05) in all the main carcass parameters measured. Diet had a significant effect (P < 0.05) on hot carcass weight. Hot carcass weight (7.6, 8.2, 8.8 kg (SEM = 0.32)) was lower (P < 0.05) for L than H with value for M being similar to L and H. In conclusion this study highlighted that Washera and Horro sheep had a similar performance under the feeding regime used in this study, and it appeared that both breeds perform better in the diet containing the highest level of concentrate used in the current study.